Can locking plate fixation of symphyseal disruptions allow early weight bearing?. Issue 10 (October 2021) - Kankanalu, Pradeep; Orfanos, Georgios; Dwyer, Jonathan; Lim, Justin; Youssef, Bishoy
Highlights: The rigid construct offered by locking symphyseal plate has the theoretical advantage of allowing patients to weight bear early. Retrospective analysis identified 46 patients (F:M 8:38) with a mean age of 46 years (range 14 to 74 years). The mean radiological follow-up period was 31 weeks with 13 (28%) patients having evidence of radiological failure. Use of locking plate for pubic symphyseal diastasis is safe and effective in allowing patients to weight bear early. Abstract: Introduction: Anterior pubic symphyseal plate fixation is the recommended treatment for disruption of pubic symphysis in an unstable pelvic ring injury. The rigid construct offered by locking symphyseal plate has the theoretical advantage of allowing patients to weight bear early. However, there are concerns of catastrophic failure about the locked plate construct. The purpose of the study was to establish if locking plate fixation for pubic symphysis disruption was effective to allow patients to mobilise weight bearing immediately after surgery. Patient and Methods: Retrospective analysis of a prospectively collected database from a single centre was performed. The study period was from 2008 to 2017. Radiographic evidence of fixation failure, revision surgery, removal of metalwork and follow up duration was noted. Results: We identified 46 patients (F:M 8:38) with a mean age of 46 years (range 14 to 74 years). Based on the mechanism of injury patients were classified into Antero-posterior compression (28), Vertical shear [10], lateral compression [4] and combined mechanism [4]. Either a 4-hole or 6-hole locking plate was used in all patients, depending on fracture extension. Posterior fixation was required in 28 (61%) patients. All patients were allowed to fully or partial weight bear. The mean radiological follow-up period was 31 weeks with 13 (28%) patients having evidence of radiological failure. Revision was performed in 1 (2%) patient, in whom the screws had pulled out of the bone. The most common mode of failure was either the screw backing out from the plate or broken screw. Among the 4 (8%) patients who had their metalwork removed, 1 (2%) had delayed onset of infection, 2 (4%) had symptoms related to backed out screw and 1 (2%) opted electively to have metalwork removed. Conclusions: With our series of patients, we have found that using locking plate for pubic symphyseal diastasis is safe and effective in allowing patients to weight bear early. A low complication rate and need for re-operation is demonstrated.